Sanguinis Students' Spatial Ability Profile - Lioni Anka Monalisa; Ifka N Hibatullah; Susanto; Saddam Hussen; Nawal Ika Susanti (Divisi Penelitian Yayasan Simfoni Ilmu Cendekia, 2026)
Spatial ability is an important ability in geometry learning. This spatial ability can be influenced by the personality type of students. One of the personality types that humans have is sanguine. Sanguine students have a problem-solving level classified as level 5. This study is a qualitative descriptive study that explains the spatial perception, spatial visualization, and mental rotation abilities of sanguine students. Data analysis used is personality questionnaire analysis, test result analysis, and interview result analysis. The research subjects were students of class X MIPA 1 SMA Negeri 1 Jember who were sanguine. The results of the study explain that sanguine students were able to fulfill every indicator of the elements of spatial perception and mental rotation, and fulfilled one indicator of the spatial visualization element. The dominant creative and innovative nature makes sanguine students able to solve mental rotation problems well.